Hierarchy Design in Metal Oxides as Anodes for Advanced Lithium‐Ion Batteries. Issue 11 (23rd August 2018) - Jin, Jun; Wu, Liang; Huang, Shaozhuan; Yan, Min; Wang, Hongen; Chen, Lihua; Hasan, Tawfique; Li, Yu; Su, Bao‐Lian
Abstract: Hierarchical structures are ubiquitous in both animals and plants. The coordination of the hierarchical structures and functions makes living organisms function efficiently. This explains why hierarchical metal oxide (HMO)‐based micro/nanostructures have recently received huge attention as anodes for application in highly efficient lithium‐ion batteries (LIBs). Indeed, hierarchy in such micro/nanostructured HMOs offers high specific surface area, stable structure, short path length, and improved higher packing density to improve the reaction kinetics and Li + /e − transport kinetics, resulting in highly enhanced rate capability and cycling stability for LIBs. This report focuses on the hierarchical design from structural, morphological, porous, and component levels to engineer the HMOs as anodes for LIBs. The advantages of micro/nanostructured HMO‐based on three reaction mechanisms (intercalation/deintercalation, conversion, and alloying/dealloying), important challenges ahead, and future perspectives on designing advanced electrode materials for next‐generation high‐performance LIBs are discussed. Abstract : Hierarchical metal oxides (HMOs) micro/nanostructures combine the characteristics of hierarchy in structural, morphological, porous, and component levels are highlighted in this report. Owing to the hierarchy presenting good monodispersity, high packing density, high surface area, and short path length, HMOs show good stability and excellent rate performance for lithium‐ion batteries via significantly enhancing the reaction and Li + /e ‐ transport kinetics.